2008
DOI: 10.1002/bip.21042
|View full text |Cite
|
Sign up to set email alerts
|

Confocal Raman microscopy on single living young and old erythrocytes

Abstract: Raman confocal microscopy, including the techniques of point Raman spectra, line mapping, 2D mapping, and time-dependent spectrum monitoring performed with 514.5 nm excitation light, was used in a comparative study on the distribution and oxidation states of hemoglobin (Hb) in young and old mature erythrocytes. It is demonstrated that in contrast to the homogeneous distribution of the Hb in young cells, there are more Hb distribution around the cell membrane in old erythrocyte. The proteins exhibit some extent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…These peaks correspond to the characteristic bands of deoxyHb[19,26,27], so it suggests that in normal pH condition hemoglobin is mainly deoxygenated. This is consistent with the results of our previous measurement on the Hb in living human erythrocyte[19]. As described previously, the samples were incubated at 4 °C for 72 hours before Raman spectroscopy measurement.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These peaks correspond to the characteristic bands of deoxyHb[19,26,27], so it suggests that in normal pH condition hemoglobin is mainly deoxygenated. This is consistent with the results of our previous measurement on the Hb in living human erythrocyte[19]. As described previously, the samples were incubated at 4 °C for 72 hours before Raman spectroscopy measurement.…”
Section: Resultsmentioning
confidence: 99%
“…To perform non-disturbance, real-time measurements on the molecular structure and oxygen carrying capacity of hemoglobin in various pH solutions, we also developed a series of novel methods of Raman confocal micro-spectroscopy[19,20]. The Raman spectra measurement was performed using a RAM INV (Horiba JY, France) system with an inverted Olympus optical microscope.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Raman spectroscopy has been used, for example, to study the mechanisms associated with RBC ageing. 86,87 In these studies, cells were separated by Percoll fractionation (where the lightest 25% were said to be the youngest and the heaviest/densest RBCs were said to be the oldest) and subjected to line mapping analysis (514.2 nm excitation). The intensity of the 1358 cm À1 band (assigned in a previous work to the symmetric half-ring stretch of pyrrole) across the samples suggested that hemoglobin was less uniformly distributed in older RBCs.…”
mentioning
confidence: 99%
“…To answer these questions, we performed scanning electron microscope (SEM) measurement and confocal Raman micro-spectroscopy on the welded recombinant chromosomes. The reason to use Raman spectroscopy [29] was that the whole chromosome can be studied without physical destruction of the chromatin, thus permitting accurate macromolecular analysis of chromosome structure. Figure 7(A) is the SEM image of the welding joint of the recombinant chromosome.…”
Section: Confocal Raman Micro-spectroscopymentioning
confidence: 99%